Efficiency Enhancement of Microwave Oven - Singhal, Ankur (My University, 2019)
Nowadays, due to the concern regarding the environment, energy-efficiency enhancement in microwave ovens are required. This dissertation works presents the efficiency enhancement of a domestic microwave oven. The performance of the oven is calculated by using the test procedure discussed in IEC 60705. According to this standard, Efficiency of oven mainly depends upon the power output and output power depends upon the rise of water temperature. The temperature rise can be achieved by more microwave absorption by the load which intern can be achieved by increasing the number of waves generated by magnetron. As per the literature, 3-D particle in cell modelling in CST studio suite software is used for the modelling of the magnetron to examine the performance of the magnetron. The geometrical parameters of the magnetron are changes to achieve the desired efficiency for the oven. Further, modelling of the π quadruple model of a non-linear transformer with doubler circuit has been done in MATLAB Simulink environment. The simulated and experimental data has been collected and compared. It is found that there is less than 5% variation in the simulated and the experimental results. Also, the performance of the oven has been enhanced by approximately 4.5%.
Keywords: Microwave oven; Magnetron; High voltage circuit; Doubler Circuit; π Quadruple Model